The influence of professional self-awareness, task complexity and AML software astuteness on money mule risk assessment among financial crime compliance officers / Mohd Irwan Abdul Rani - Abdul Rani, Mohd Irwan (2024)
The threat of money mule has placed the financial system in a great peril by lending their account to layer illicit funds. The trend of money mule is showing a deteriorating pattern in several jurisdictions, such as United Kingdom, European Union and Hong Kong. Unfortunately, the same situation has beleaguered Malaysia with money mule continues to become an emerging financial crime threat. The objective of this study is to explore the Judgement and Decision-Making (JDM) in money mule risk assessment among financial crime compliance officers by investigating the influence of professional self-awareness, task complexity and AML software astuteness on money mule risk assessment. This study also uses task complexity as a moderator between professional self-awareness, AML software astuteness and money mule risk assessment. The data collection process was performed under non-probability judgement sampling, with 158 samples returned for analysis. The preliminary data analysis yielded 149 usable for further evaluation. The measurement and structural model assessments were conducted using Structural Equation Modelling using Partial Least Square (PLS-SEM). In assessing the direct effect of internal factor, objectivity is found to have significant influence on money mule risk assessment. Meanwhile, the external factors’ variables of transaction analysis and STR drafting are found to significantly influence money mule risk assessment. Six moderating relationships have demonstrated significant results, proving that task complexity is an effective moderator. There are several limitations in this study, in which the financial crime compliance officers do not have a registered body that governs them and thus a proper sampling frame could not be obtained. The coverage of money mule risk assessment in this study does not include other agencies that are responsible in combatting money mule problem, such as investigation officers from Royal Malaysia Police (RMP) and Financial Intelligence Unit (FIU). Hence, the holistic framework of JDM in money mule risk assessment is not wholly represented. This study has developed the novel money mule risk assessment, by assimilating the Know-Your-Customer (KYC) and transaction monitoring money mule red flags. Shadowed by the domination of audit-related JDM studies, the findings in this study have also added a new money mule risk assessment exploratory study to the body of knowledge. It is hoped that the findings reported in this study have filled the gap in the financial crime compliance area, and shall contribute to a more effective blueprint to combat money mule phenomenon.